Combined Effects of Proton Radiation and Simulated Microgravity on the Cell Viability and ALP Activity of Murine Osteoblast Cells - Liqiu Ma; Liqiu Ma; Fuquan Kong; Fuquan Kong; Yihao Gong; Yihao Gong; Qiaojuan Wang; Qiaojuan Wang; Jiancheng Liu; Jiancheng Liu; Li Sui; Li Sui (Frontiers Media S.A., 2021)
Proton radiation (PR) and microgravity (μG) are two key factors that impact living things in space. This study aimed to explore the combined effects of PR and simulated μG (SμG) on bone function. Mouse embryo osteoblast precursor cells (MC3T3-E1) were irradiated with proton beams and immediately treated with SμG for 2 days using a three-dimensional clinostat. All samples were subjected to cell viability, alkaline phosphatase (ALP) activity and transcriptome assays. The results showed that cell viability decreased with increasing doses of PR. The peak ALP activity after PR or SμG alone was lower than that obtained with the non-treatment control. No difference in cell viability or ALP activity was found between 1 Gy PR combined with SμG (PR-SμG) and PR alone. However, 4 Gy PR-SμG resulted in decreased cell viability and ALP activity compared with those obtained with PR alone. Furthermore, Gene Ontology analysis revealed the same trend. These results revealed that PR-SμG may lead to reductions in the proliferation and differentiation capacities of cells in a dose-dependent manner. Our data provide new insights into bone-related hazards caused by multiple factors, such as PR and μG, in the space environment.